Effects of cadmium chloride as inhibitor on stability and kinetics of immobilized Lactoperoxidase(LPO) on silica-coated magnetite nanoparticles versus free LPO - Narges Babadaie Samani; Hashem Nayeri; Gholamreza Amiri Amiri (Nanomedicine Journal, 2016)
Objective(s): Enzyme immobilization via nanoparticles is perfectly compatible against the other chemical or biological approximate to improve enzyme functions and stability. In this study lactoperoxidase was immobilized onto silica-coated magnetite nanoparticles to improve enzyme properties in the presence of cadmium chloride as an inhibitor. Materials and Methods:  The process consists of the following steps: (1) preparing magnetic iron oxide nanoparticles using the co-precipitation method, (2) coating NP with silica (SiO2) by sol–gel reaction, (3) characterizations of NPs were examined by FT-IR, XRD, AGFM and TEM. (4) Immobilization of LPO on the magnetite NPs, (5) Study kinetic and stability of both free and immobilized LPO in the presence of various concentrations of cadmium chloride. Results:  The size of the Fe3O4 and silica-coated magnetite nanoparticles were about 9 nm and 12 nm, respectively. The results showed that the highest immobilization yield, nearly 90 %, was attained at 240 to 300 µg of LPO at 15h. It was found that the concentration of cadmium chloride directly affects the LPO activity and changes the kinetic parameters of it. Also, the results showed that immobilized LPO has better tolerance than the free LPO, so that after immobilization, Vmax of immobilized LPO was increased and Km of immobilized LPO was decreased. Conclusion: The results demonstrating that the effect of immobilized lactoperoxidase on silica-coated magnetite nanoparticles increases the stability of the LPO in the presence of cadmium chloride as inhibitor. Michaelis–Menten parameters (Km and Vmax) also revealed the considerable improvement of immobilized.